PROSPECTS AND PROBLEMS OF TOURISM INDUSTRY IN ASSAM - et al., Miss Ananya Borgohain (International Journal of Control and Automation, 2020)
Tourism is now-a-days considered as an important industry which has vast scope for the generation of income and employment. It is one of the world’s fastest growing industries, a major source of foreign exchange earner of a nation and a measure for resolving interstate and inter community conflict. Although the whole north eastern region has tremendous tourism potential, the tourism industry in the area is still miles to go to exploit the proper potentialities. This is mainly due to curse of nature and lack of proper attention of the central government. The state as well as the entire north east region of India has been subjected to century long neglect. Even after 64 years of the country’s independence, same kind of central apathy is being continued to the region. The state of Assam is best known for her unique natural beauty with flora and fauna, historical monuments, pilgrim centre, tea gardens and its colorful cultural festivals. All these can make Assam as one of the best destination of the tourists. The tourism in Assam is mainly based on Wildlife, Tea tourism, Historical Monuments Ethnic cultural heritages etc. Therefore, natural parks and sanctuaries, rivers, lakes, warm water springs, forests, wild life, are the principal components of tourist attraction in the state. The whole tourism potentialities of the state can be grouped together under the categories - Wildlife, Nature Tourism, Tea tourism, Eco Tourism, Cultural Tourism, and Adventure Tourism etc. The present paper has been an attempt to highlight the main prospects and problems of tourism in Assam. The development of tourism in the state during the globalization period has also been analysed on the basis of some secondary data.